PERSEPSI PERSONIL SALON KECANTIKAN TENTANG KOMPETENSI PSIKOMOTOR MAHASISWA D4 PENDIDIKAN TATA RIAS DAN KECANTIKAN DALAM PELAKSANAAN PENGALAMAN LAPANGAN INDUSTRI (PLI) DI KOTA PADANG - Saputri, Riska Desriani; Katin, Yusmar Emmy; Hayatunnufus, Hayatunnufus (Journal of Home Economics and Tourism, 2012)
The goal of this research is describing the perception of beauty salon personnel about psychomotor competency of university students in doing activity such as (1) face makeup, (2) skin’s face care, (3) hair style and care, (4) hair barbering, (5) body care, (6) face makeup, skin’s face care, hair style and care, hair barbering,  and body care. Measuring tool in this research use questionnaire that has been tested its validity and reliability, then the questionnaire is analyzed by determining frequency distribution that is continued with clarifying it based on ideal mean and ideal deviation standard. The result of this research show that the perception of beauty salon personnel about psychomotor competency of students with average scores of the higher respondent at : (1) face makeup with 33% score in medium category, (2) skin’s face care with 33% score in medium category , (3) hair style and care with 31% score in medium category, (4) hair barbering with 33 % in very low category , (5) body care with 24 % in medium category (6) face makeup, skin’s face care, hair style and care, hair barbering, and body care with 48,9 % in medium category.